Активизация студентов на занятиях по политологии с использованием интерактивных методов обучения - Великая, О.В. (My University, 2016)
Activation of the students in the classroom is always relevant in teaching at the college or university. The author of the article offers an interactive learning methods that promote more successful learning. All the proposed techniques were tested in the classroom in political science and is now widely used in training. All this shows what tremendous opportunities and a wide field of activity carry the perceived creative methods and forms of work with students.
Keywords: political science; interactive teaching methods; students; interdisciplinary communication